2020
DOI: 10.1183/13993003.01104-2019
|View full text |Cite
|
Sign up to set email alerts
|

EAN/ERS/ESO/ESRS statement on the impact of sleep disorders on risk and outcome of stroke

Abstract: @ERSpublicationsEvidence suggests a bidirectional relationship between sleep and stroke. However, the pathophysiological base of the associations and the possibilities of improving prevention and outcome through sleep-related interventions require further evaluation.ABSTRACT Sleep disorders are highly prevalent in the general population and may be linked in a bidirectional fashion to stroke, which is one of the leading causes of morbidity and mortality.Four major scientific societies established a task force o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0
11

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(68 citation statements)
references
References 160 publications
(217 reference statements)
1
56
0
11
Order By: Relevance
“…In a systematic review of stroke and TIA patients, 10 studies all reported that BSD increased vascular events or mortality [52]. BSDs might improve with stroke recovery but elevated mortality continuously after the acute stage [53,54].…”
Section: Breathing-related Sleep Disorders (Bsds) and Strokementioning
confidence: 99%
“…In a systematic review of stroke and TIA patients, 10 studies all reported that BSD increased vascular events or mortality [52]. BSDs might improve with stroke recovery but elevated mortality continuously after the acute stage [53,54].…”
Section: Breathing-related Sleep Disorders (Bsds) and Strokementioning
confidence: 99%
“…Overall, after adjusting for potential confounders (age, sex, body mass index, smoking, hypertension, and diabetes), untreated OSA conveys a 2 -fold increased risk of stroke. 70 Several prospective studies have shown an independent association of moderate -severe OSA and stroke. In the WSCS, an AHI of more than 20 events/h of sleep was associated with an increased risk of stroke over the subsequent 4 years.…”
Section: Coronary Artery Disease / Ischemic Heart Diseasementioning
confidence: 99%
“…78 Furthermore, a meta -analysis of available RCTs failed to demonstrate benefit of CPAP treatment on stroke risk reduction, although patients who are adherent (>4 hours per day) may still benefit and thus, a trial of treatment may still be justified. 70 The ongoing Sleep SMART (Sleep for Stroke Management and Recovery Trial) is a multisite prospective RCT whose primary outcome is to determine the effect of CPAP on reducing stroke recurrence, incidence of ACS and all -cause mortality, cardiovascular mortality in patients with central sleep apnea treated with adaptive servo-ventilation (servo -controlled inspiratory pressure support on top of expiratory positive airway pressure). Posited reasons for this negative outcome included a reduction in cardiac output with positive airway pressure in some patients, or a possible beneficial aspect to the Cheyne -Stokes respiration seen in central sleep apnea and eliminated by adaptive servo-ventilation.…”
Section: Coronary Artery Disease / Ischemic Heart Diseasementioning
confidence: 99%
“…A meta-analysis of 23 cohorts estimated the risk of having difficulties falling asleep, having difficulties maintaining sleep, early morning awakening and non-restorative sleep. Difficulties both falling asleep and maintaining sleep were associated with an increased risk of CVD events 29,30 On the other hand, sufficient sleep duration in addition to all four traditional healthy lifestyle factors (physical activity, nutrition, smoking and alcohol intake) was associated with 65% lower risk of CVD and 83% lower risk of fatal CVD in one large European cohort 31 However, it is still unknown whether the association of insomnia with cardio-metabolic risk is causal due to reverse causation bias and residual confounding factors inherent to observational studies.…”
Section: Re Sults/cons Ensus S Tatements Session 1-public Health and Insomniamentioning
confidence: 99%